State, security and cyberwar : the quest for digital peace - Singh, Thangjam K.; Jha, Sanjay K. (Routledge, 2026)
This book examines the complex interactions amongst states and security apparatuses in the contemporary global order, and the prospect of peace with the emergence of cyberwarfare. Analysing why states consider cyberspace as a matter of security and strategic concerns, it looks forward to a possible foundation of 'cyberpeace' in the international system. It examines the idea of cyber-territory, population, governance, and sovereignty, along with that of nation states referring to great, middle, and small powers.The book explores the strategic and security aspects of cyberspace along with the rational behaviours of states in the domain. It explains the militarisation and weaponisation of cyber technologies for strategic purpose and traces the progression of cyber war and its impact on global stability. The last section of the book examines the possibility of building peace in che cyber domain with the endeavours of the international community to safeguard cyber sovereignty and promote stability in the digital sphere.It also discusses India's position on digital security, cyberwarfare, and the pursuit of cyberpeace. The book offers valuable insights for students, researchers, practitioners, stakeholders working in and on military and strategic affairs, peace and conflict studies, and global politics, as well as interested general readers.